1992
DOI: 10.1002/for.3980110202
|View full text |Cite
|
Sign up to set email alerts
|

Co‐integration, error correction and improved medium‐term regional VAR forecasting

Abstract: This study investigates possible improvements in medium-term VAR forecasting of state retail sales and personal income when the two series are co-integrated and represent an error-correction system. For each of North Carolina and New York, three regional vector autoregression (VAR) models are specified; an unrestriczed two-equation model consisting of the two state variables, a five-equation unrestricted model with three national variables added and a Bayesian (BVAR) version of the second model. For each state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
0
28
1
Order By: Relevance
“…In the studies by LeSage (1990) and Shoesmith (1992), the ECM was found to outperform the VAR model in forecast accuracy, particularly over long horizons. As the underlying equilibrium relationship in the EC model is expected to hold only in the long run, better performance should be more evident in the long run (see Stock, 1995).…”
Section: Forecast Performancementioning
confidence: 93%
“…In the studies by LeSage (1990) and Shoesmith (1992), the ECM was found to outperform the VAR model in forecast accuracy, particularly over long horizons. As the underlying equilibrium relationship in the EC model is expected to hold only in the long run, better performance should be more evident in the long run (see Stock, 1995).…”
Section: Forecast Performancementioning
confidence: 93%
“…with f(i, j) = 1, if i = j and ij k otherwise, with (  01 Kinal and Ratner (1986) and Shoesmith (1992) …”
Section: The Prior Variancesmentioning
confidence: 99%
“…Given that, we have domestic as well as foreign and world variables within the 266 data series used for the large-scale models, and realizing that South Africa is a small open economy, and, hence, domestic variables would have minimal, if any, effect on foreign and world variables, while, the latter set of variables is sure to have an influence on the South African variables, setting ij k = 0.5 could be quite far fetched from reality. Hence, borrowing from the BVAR models used for regional forecasting, involving both regional and national variables, and following Kinal and Ratner (1986), Shoesmith (1992) and Gupta and Kabundi (2008b) …”
Section: The Var and Bvarsmentioning
confidence: 99%